EFFECT OF RECIPROCAL PEER TUTORING ON READING ACHIEVEMENT OF PRIMARY SCHOOL PUPILS IN AWKA SOUTH METROPOLIS - Anidi, Charles A.; Obumneke-Okeke, Ifeoma M. (Journal of Early Childhood and Primary Education, 2020)
Observations and experiences by researchers in Nigeria have shown that pupils lack reading and comprehension skills and as a result, perform poorly in reading comprehension. There is, therefore, the need for instructional approach that make children strategic readers. This study investigated the effect of reciprocal peer tutoring on reading achievement of primary school pupils in Awka Metropolis in Awka South Local Government Area. Three research questions guided the study. Two null hypotheses were tested at 0.05 level of significance. The study adopted a quasi-experimental design specifically the pre-test, post-test design. The population comprised 3,419 primary five pupils in Awka metropolis and 65 pupils selected from schools that use Macmillan English who participated in the study formed the sample. Reading Achievement Test (RAT) was used as an instrument for data collection. The reliability coefficient for RAT using Kuder-Richardson Formula 20 was 0.89. Pupils in the experimental group were taught reading using reciprocal peer tutoring while those in the control group were taught reading using conventional method which is lecture method. Data collected were analysed using mean scores for research questions and Analysis of Covariance (ANCOVA) for testing the hypotheses. Major findings revealed that pupils taught reading with Reciprocal Peer Tutoring (RPT) performed significantly better than those taught with conventional method. There was no significant difference in the performance of male and female pupils taught reading with RPT. Based on the findings, it was recommended that RPT should be adopted by teachers for teaching English comprehension in the primary schools. Workshop and conferences on the use of reciprocal peer tutoring in teaching and learning of reading should be organized for teachers by school authorities and educational administrators at least annually.